Upaya Kemenag Samarinda Mewaspadai dan Menolak Keterlibatan Kelompok Yang Membawa Paham Radikalisme Agama di MAN 1 Samarinda - Putri Amelinda; Mohammad Taufik (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This research aims to find out and describe the perceptions of MAN 1 Samarinda residents regarding religious radicalism. This research uses three indicators, namely perception, effort and inhibiting factors to determine whether to be wary of and reject the involvement of groups that carry religious radicalism at MAN 1 Samarinda. The data collection technique used was purposive sampling. The research results show that MAN 1 Samarinda has adopted various proactive strategies to overcome religious radicalism, including improving the religious education curriculum which emphasizes moderation, tolerance and diversity. The school is also active in holding extracurricular activities, such as seminars, discussions and workshops, which aim to increase students' awareness and understanding of the dangers of radicalism. Apart from that, MAN 1 Samarinda also works closely with students' parents and the local community to build strong partnerships in monitoring and preventing potential radicalism. This collaboration is important in creating a safe and supportive school environment for all members of the school community. This research concludes that a holistic approach involving various stakeholders, such as students, teachers, school staff, parents and the community, is key in efforts to be aware of and reject the involvement of groups that carry religious radicalism at MAN 1 Samarinda. The implication of this research is that moderate and tolerant education needs to continue to be encouraged as part of a strategy to prevent religious radicalism in schools.